(untitled) (Altre Modernità, 2022)
Intimate diaries tend to be highly vulnerable texts as they face self-censorship, little recognition in the cultural field and even destruction when they are left in the hands of descendants. The Chilean writer José Donoso left eighty notebooks that he began in 1950 and wrote until practically his death in 1996. If the writer did not publish them during his lifetime, why publish them post-mortem? And what is more relevant, under what criteria? This article aims to highlight the value of José Donoso’s intimate diaries, to consider how they dialogue with his narrative work and, in particular, how to deal with the complexity involved in their publication.